(untitled) (Altre Modernità, 2013)
The landscape plays a leading role in the poetry of Antonio Machado (1875–1936), whose “simple love of Nature” is innate, inherited within his family environment and cultivated during his formative years at the Instituciόn Libre de Enseñanza. According to an original reversal of the traditional aesthetic perspective, the poet shows a peculiar interest towards the imperceptible and insignificant vegetal specimens (“nimios”) of the peninsular “emotional lanterns”. This bifronted author offers a fruitful intersection between the fields of Natural Sciences and Humanities and constantly mentions a diverse range of plants, trees, herbs and flowers, which are seen, remembered, dreamed or imagined; these botanic elements are filtered through the naturalist’s meticulous look and, at the same time, the poet’s emotional prism, who emerges as the living embodiment of post-romantic dialectic between Symbolism and Existentialism. The paysage de l’âme of the “old Spanish tree” (a famous metaphor by Pablo Neruda to describe Machado) is captured in the herbs and fruit trees of his Sevillian “huerto”, the domestic garden where the lyrical subject projects the melancholy of his first Soledades (1903); or in the varied tree species of Castilian vegetation, which are a symbol of past glory against present decadence, according to the ’98 generation’s view of Campos de Castilla (1912); or, last but not least, in the plants of the rarefied and idealized landscape of Nuevas canciones (1924).